Tissue plasminogen activator modified thromboelastography identifies fibrinolysis resistance in dogs with immune-mediated hemolytic anemia - Goggs, Robert; Davis, Samantha; Brooks, Marjory B. (Frontiers in Veterinary Science, 2025)
IntroductionImmune-mediated hemolytic anemia (IMHA) is an important immunologic disorder in dogs that is associated with high mortality rates, frequently due to thromboembolism. Multiple factors contribute to the pathophysiology of thrombosis in IMHA including intravascular tissue factor expression, platelet activation, and neutrophil extracellular trap (NET) formation. It was hypothesized that dogs with IMHA have impaired fibrinolysis that can be detected using a modified viscoelastic assay and that biomarkers of NET formation are associated with this hypofibrinolysis.MethodsTwenty dogs with non-associative IMHA were enrolled and paired thromboelastography (TEG) assays with and without additional tissue plasminogen activator (tPA) performed. A panel of hemostasis tests including measurement of plasma thrombin-activatable fibrinolysis inhibitor (TAFI) activity, active plasminogen activator inhibitor-1 (PAI-1), and concentrations of cell-free DNA (cfDNA) and nucleosomes were also performed.ResultsDogs with IMHA had hypercoagulable TEG tracings, increased TAFI activity and frequently displayed fibrinolysis resistance defined as minimal lysis in tPA augmented TEG assays. Increased concentrations of cfDNA, nucleosomes and active PAI-1 in dogs with IMHA compared to healthy controls were identified.DiscussionThese observations support the hypothesis that hypofibrinolysis is a common feature of IMHA in dogs. Increased plasma active PAI-1 concentrations and TAFI activities might contribute to the observed hypofibrinolysis. The combined hypercoagulability and hypofibrinolysis observed supports recent recommendations to provide thromboprophylaxis to all dogs with IMHA. These findings also suggest that NETosis might contribute to the common prothrombotic imbalance of IMHA in dogs.